Noise Exposure and Hearing Threshold Profile among Zumba Fitness Regulars in Kuantan, Pahang, Malaysia - A, Razali; MS, Othman; MS , Rahman; NFI , Misaridin (IIUM Medical Journal Malaysia, 2020)
INTRODUCTION: Recreational noise exposure has become a major threat to the hearing system, and this includes exposure to loud noise during group exercises such as Zumba Fitness, where loud music plays an important role. This study aimed to assess the noise exposure and hearing threshold profile among Zumba Fitness regulars in Kuantan, Malaysia. MATERIALS AND METHODS: Noise exposure and hearing profile threshold were measured during Zumba Fitness sessions at a fitness studio in Kuantan, Malaysia from 24th June 2014 to 12th August 2014. Noise exposure was measured using a noise dosimeter for one hour of Zumba Fitness session with a total of nine sessions run by three different instructors while sound level pressure was taken using a sound level meter during ambient, peak session and during cooling down. Thirty participants answered questionnaires and underwent pure tone diagnostic audiometry test at a local clinic for hearing threshold documentation. RESULTS: Some areas of the hall posed higher risks of causing noise-induced hearing loss especially near the amplifiers. There were periods when the hearing level exceeded 115 dBA. Early abnormal pattern could be observed in the hearing profiles of some of the participants to suggest preliminary hearing problems. CONCLUSION: Zumba Fitness regulars have a risk of developing noise-induced hearing loss and preventive steps should be properly addressed as NIHL is permanent and irreversible.